In Vitro Pathogenicity Test Of Binucleate Rhizoctonia AND Rhizoctonia solani On Mung Bean (Mgna radiata L. WUczeck) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT Kasiamdari, R.S. 2004. In Vitro Pathogenicity Test of Binucleate Rhizoctonia andRhizoctonia solani on Mung Bean (Vigna radiata L. WUczeck). Biologi 3 (4) : 267- 276. Binucleate Rhizoctonia and Rhizoctonia solani belong to a group of Basidiomycetous imperfect fungi, and have been known to attack a variety of host plants. In vitro experiment was conducted to investigate the pathogenicity of the isolate of BNR (AG-Bo) on mung bean in comparison to three isolates ofR. solani (AG1-1C, AG2-1 and AG2-2IIIB), and to assess their influence on plant growth. Results showed that the mean disease severity due to BNR AG-Bo on leaves was very low compared to any of the R. solani. The BNR AG-Bo did not cause disease symptoms on stems, whereas the/?, solani AGl-lChadthe highest mean disease severity rating on stem followed by AG2-2IHB and AG2-1. The mean disease severity due to BNR AG-Bo on roots was less than that due to the isolates ofR. solani AG1-1C and AG2-2IHB, but greater than AG2-1. BNR Ag-Bo was able to infect 40% of the root, which was greater man the infection by R. solani AG2-1 (28%), but less than the infection by R. solani AG1-1C (52%) or AG2-2IHB (97%). Fourteen days after inoculation, the BNR AG-Bo and R. solani AG2-1 had no significant effect on the root length of mung bean, whereas R. solani AG1-1C and AG2-2IHB reduced the root lengths. The BNR AG-Bo and R. solani AG2-1 did not reduce total fresh weights of plants, whereas/?. 5o/a/Â»AGl-lCandAG2-2IIIBreducedthetotalfreshweights,